From the history of teaching Russian language and literature at the old Vilnius University - Kaupuža, A. (Literatūra, 1969)
The biography as well as activities of the Russian philologist Professor I. N. Cherniavsky at the Vilnius University in the beginning of the 19th century have been little investigated.A close study of the material found in archives enabled the author to present a general idea about his lectures and to restore some biographical facts.The investigation of university syllabi and examination questions resulted in the following: the information, communicated by I. N. Cherniavsky, was extensive, he was a man of great learning in his field and was a warm propagandist of Russian literature and culture.
Keywords: -